ANALISIS MANAJEMEN PROSES PERSIAPAN PUSKESMAS MENUJU PUSKESMAS PELAYANAN OBSTETRI DAN NEONATAL EMERGENSI DASAR DI KABUPATEN PATI TAHUN 2014 - Wiwik Wulandari; Anneke Suparwati; Putri Asmita Wigati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
The health service of obstetrics and Neonatal Emergency Basis is an inpatient Clinics that are able to conduct civil defence emergency obstetric and neonatal care or basic level of complication in 24 hours a day and 7 days a week. The results of the preliminary survey noted that the preparation of health equipment and drugs have been provided but all health care Facilities but will not match the manual can only approach the course. The purpose of describing all aspects of the preparatory process of the management of clinics to PONED. Type of this research is descriptive research with qualitative methods. The object in this research is the management process of preparation clinics to PONED, whereas the subject of research is the primary informant and the informant triangulation. Data collection methods in the research of in-depth interviews as well as observation and documentation, research results show that HR planning: none of the Clinics, lack of budget funds from the Government, it still happened the delay in reporting as well as for his reference to the grooves are still utilizing the hospital nearest the C type because the Starch has only one Hospital PONEK, less routine agenda to schedule the most scrutiny is only 1 x a year though. These three variables are grouped into factors Stength, overrun Weakness, Opportunity, and the result of factors of weakness Threath is greater than the strength of the conclusion that the preparation process management not ready a hundred percent because a trained human resources are still lacking, Health care facilities as well as the budget of the Fund. The recommendations of this study are: To Health Office made the planning of human resources, health care facilities as well as the operational funds, imposed strict sanctions related reporting, regularly scheduled agenda pengawasannya. Suggestions for public health: should make detailed planning needs of clinics, improve cross-sectoral partnership, more discipline in reporting activities